The Violation of Maxims in Indonesian Speech of Mental Retardation Child - Ira Eko Retnosari; Kisyani Kisyani; Bambang Yulianto (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2020)
This article aims to describe the violations of the maxims in the Indonesian speech of mentally retarded children. This study used a descriptive qualitative method. The data source of this study is one mild mental retardation child. The data of this research are words, phrases, and sentences that contain violations of the maxims in the principle of cooperation. Data collection techniques in this study were observation, stimulating, recording, and field recording. Data collection procedures in this study include entering the field, making observations, recording speeches, transcribing field records, entering data in tables, validating data that has been collected. In analyzing the data, a pragmatic equivalent analysis method is used. Data analysis procedures in this study are reducing data, presenting data, interpreting data, and concluding. In analyzing the data, a pragmatic equivalent analysis method is used. Data analysis procedures in this study are reducing data, presenting data, interpreting data, and concluding. The results of the data analysis of this study are the maxima violation that most children with mental retardation are the maxim of relations. That is because the research subject often changes the topic of speech. The research subject often changes the topic because he is not interested in talking about topics.